2015
DOI: 10.1016/j.jped.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, school backpack weight, and nonspecific low back pain in children and adolescents

Abstract: Girls had higher disability and lower QoL than boys in the domains of physical and emotional functioning, psychosocial health, and physical health summary scores, and on the total PedsQL score; however, similar school backpack weight was reported. Participants with LBP revealed lower physical functioning and physical health summary score, yet had similar school backpack weight to those without LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 26 publications
5
32
1
3
Order By: Relevance
“…In investigating the associated factors of this study, it was observed that individuals who had impact on HRQoL were mostly girls, with moderate or severe communication skills and poor general health, according to caregivers. The higher frequency of impact on HRQoL in girls with CP, although the lifestyle of individuals with CP is similar, regardless of gender, may be related to biological factors such as hormone production and differences in biological maturation …”
Section: Discussionmentioning
confidence: 98%
“…In investigating the associated factors of this study, it was observed that individuals who had impact on HRQoL were mostly girls, with moderate or severe communication skills and poor general health, according to caregivers. The higher frequency of impact on HRQoL in girls with CP, although the lifestyle of individuals with CP is similar, regardless of gender, may be related to biological factors such as hormone production and differences in biological maturation …”
Section: Discussionmentioning
confidence: 98%
“…For many years, LBP in children and adolescents was considered as a sign of serious disease 59,60. Higher prevalence rates of nonspecific LBP were epidemiologically reported in children than adults as a result of some biological risk factors that increase in rates during adulthood 61,62.…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo com a falta de um valor de referência exato para o peso das mochilas escolares, a grande parte dos profissionais consente que elas não devem exceder 10% da massa corporal do aluno. 17 De um total de 206 mochilas pesadas, 148 delas estavam acima dos 10% recomendados, o que equivale a 71,84% da população escolar avaliada.…”
Section: Resultsunclassified